1159 Long Term Growth of Extremely Low Birth Weight Indian Infants at Corrected Age 1 Year. (October 2012) - Mukhopadhyay, K; Mahajan, R; Kumar, P
Abstract : Background and Aims: Inspite of increasing survival of ELBW infants in India there is significant paucity of data on their long term growth. The aim of our study was to assess growth of ELBW infants at corrected age 1 year. Methods: Prospective observational study conducted in the follow up clinic of a level III neonatal unit. Forty eight ELBW infants discharged from neonatal intensive care unit were followed for weight, length and Head circumference at corrected age (CA) 1 year and z-scores were calculated. Results: The mean (SD) birth weight and gestation were 872±82 g and 29.9±2.3 weeks. At CA 1 year, as per WHO growth charts (2006), growth at < 3 rd centile was observed in 60.4% infants for weight, 54% for length and 58.3% for HC. Growth was more than 50 th centile in 6.3% infants for weight, 4.2% for length and 2.1% for HC. Z-scores of 0 and above was recorded in 9% infants for weight and 7% for length. Twenty eight babies (58%) were SGA. SGA infants were smaller in weight (856±87 g vs 901±66 g, p=0.023), higher in gestation (30.9±1.9 wks vs 28.2±1.8 wks, p=0.000) and discharged earlier (p=0.003) than AGA. There was no difference in growth parameters between SGA and AGA and male and female at CA 1 year. Conclusion: ELBW infants had significant growth failure at CA 1 year and intergroup differences between SGA and AGA were not observed.